2020
DOI: 10.1016/j.heliyon.2020.e04844
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of cardiomyocyte-like cells from human amniotic fluid mesenchymal stem cells by combined induction with human platelet lysate and 5-azacytidine

Abstract: Human amniotic fluid mesenchymal stem cells (hAF-MSCs) have been shown to be effective in the treatment of many diseases. Platelet lysate (PL) contains multiple growth and differentiation factors; therefore, it can be used as a differentiation inducer. In this study, we attempted to evaluate the efficiency of human platelet lysate (hPL) on cell viability and the effects on cardiomyogenic differentiation of hAF-MSCs. When treating the cells with hPL, the result showed an increase in cell viability. Expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…In addition, cTnI level was significantly higher in 5-aza-treated groups compared to control group. Our results are in line with studies showing successful differentiation of MSCs into cardiomyocytes by 5-aza treatment (11,14,(36)(37)(38). These studies have confirmed the increased expression of cardiac specific genes such as cardiac troponins, GATA4, myosin heavy chain in 5-azatreated MSCs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, cTnI level was significantly higher in 5-aza-treated groups compared to control group. Our results are in line with studies showing successful differentiation of MSCs into cardiomyocytes by 5-aza treatment (11,14,(36)(37)(38). These studies have confirmed the increased expression of cardiac specific genes such as cardiac troponins, GATA4, myosin heavy chain in 5-azatreated MSCs.…”
Section: Discussionsupporting
confidence: 91%
“…Synthetic agents are preferred because they are more stable than protein-based growth agents, have a longer half-life, and do not require living organisms for synthesis. 5-aza has been shown to induce the differentiation of stem cells into a variety of cells, including cardiomyocytes (11,14,36). Although the mechanism by which 5-aza promotes cardiomyogenic differentiation remains unclear, it has been shown that it effectively induced the up-regulation of cardiomyogenic specific genes such as cTnT, cTnI, α-cardiac actin and Nkx2 through the ERK pathway (13,22).…”
Section: Discussionmentioning
confidence: 99%
“…So far, several kinds of stem cells, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) are proven to be pluripotent, giving rise to all the cells from the three embryonic germ layers [13,14]. Evidence has accumulated that both murine and human adult tissues contain early-development stem cells with a broader differentiation potential than other adult monopotent stem cells [15,16]. The nonhematopoietic stem cells appear to be heterogeneous and contain cells committed to mesenchymal and endothelial lineages, as well as more primitive multipotential cells resembling progenitors of germ cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…So far, several kinds of stem cells, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) are proven to be pluripotent, giving rise to all the cells from the three embryonic germ layers [13,14]. Evidence has accumulated that both murine and human adult tissues contain early-development stem cells with a broader differentiation potential than other adult monopotent stem cells [15,16]. The nonhematopoietic stem cells appear to be heterogeneous and contain cells committed to mesenchymal and endothelial lineages, as well as more primitive multipotential cells resembling progenitors of germ cells [17].…”
Section: Discussionmentioning
confidence: 99%